Anthelmintic activity of extracts of Coriandrum sativum linn. In indian earthworm - Chandan H.S.; Tapas A.R.; Sakarkar D.M. (International Journal of Phytomedicine, 2011)
Coriandrum sativum Linn. (CSL) is popularly known as coriander in India belongs to family Apiaceae. The objective of the present work was to evaluate the in-vitro anthelmintic potency of the ethanolic extract and carbon tetrachloride extract of Coriandrum sativum Linn. plant using Indian earthworms (Pheretima posthumad). The various concentrations (50, 100, and 150 mg/ml) of the ethanolic extract and carbon tetrachloride extract were tested in-vitro for anthelmintic potency by determination of time of paralysis and time of death of worm. Piperazine citrate (15mg/ml) used as standard. The result of present study indicates that the Coriandrum sativum Linn. potentiate to paralyze earthworm and also caused its death after some time. The shortest time of paralysis was observed at higher dose (150 mg/ml) of both ethanolic extract and carbon tetrachloride were found to 28 min and 45 min respectively. The results of the study are comparable to standard Piperazine citrate. The result showed that ethanolic extract of Coriandrum sativum Linn. took less time to cause paralysis of the earthworm than that of carbon tetrachloride extract Coriandrum sativum Linn.. Thus the present study demonstrate that the Coriandrum sativum Linn. as an anthelmintic has been confirm as the ethanolic and carbon tetrachloride extracts of whole plant displayed activity against the earthworm used in study.